Survival analysis of chronic kidney disease patients with hemodialysis - Kuwat Susanto; Asiandi (Proceedings Series on Health & Medical Sciences, 2020)
The incidence of Chronic Kidney Disease (CKD) is increasing every year. The prevalence of CKD patients in Indonesia is 0.2%. One of the management of CKD is hemodialysis. The benchmark of success in hemodialysis therapy in extending the life of the patient is a survival rate. Through this survival rate, it will be visible to see the duration of the patient can survive. Objective: This study aimed to determine the factors which affected the survival time of Chronic Kidney Disease patients undergoing hemodialysis in Banyumas Regional Hospital. This study implemented an observational analytic design. This research type was a retrospective cohort. This study involved 275 respondents selected through simple random sampling technique. The setting of the study was in the Hemodialysis Room of Banyumas Regional Hospital. Research variables were tested by Kaplan meier method. The analysis indicated that the occupation and vascular access significantly affect the survival rate of patients with the Chronic Kidney disease. The result of the significance (p-value) was smaller than 0.05.There is a correlation between factors that affected the survival rate and the time of life resistance of CKD patients undergoing hemodialysis at Banyumas Regional Hospital, which are occupation and vascular access.